PELATIHAN KOMPETENSI KOMUNIKASI BAGI ANGGOTA KARANG TARUNA PADU SELARAS RW 06 DI KECAMATAN CIBURIAL BANDUNG - Ditha Prasanti; Sri Seti Indriani (LPPM UNINUS, 2017)
This article is the result of Community Service Activities (PKM) which has been done by the author on members of Karang Taruna Padu Selaras in Cirapuhan village, Kec. Ciburial, Bandung. PKM activities conducted are about Communication Competency Training for Coral Reef Members Padu Selaras in Cirapuhan village, Kec.Ciburial, Bandung. Community Service Activities has the objective of producing outcomes, namely: 1) Providing concrete knowledge and insight on communication competency training; 2) Provide basic skills on communication competence for members of Karang Taruna Padu Selaras. The method of PKM implementation conducted in this training activity is ice breaking method; lecture method; Group discussion methods; And feedback collection methods. The conclusions of this communication competency training are: (1) As a benchmark for members of Karang Taruna Padu Selaras in understanding the communication competence (2) Increasing their awareness of the importance of having good and right communication competence; (3) Improving the basic capability of members of the Parang Taruna Padu Synchronized in communicating.